Critical analysis of harassment in the changing workplace: how the courts developed the definition of sexual harassment and the parameters of the employer's responsibility in curbing this problem - Gibson, Kirsty Anne (University of the Witwatersrand, Johannesburg, 2023)
The definition of the workplace is changing as more employee's start to work remotely. This change in the workplace will affect the manner in which employees communicate and engage with one another. It will also change the manner in which employees are harassed within the work environment. Sexual harassment has been regulated in South Africa for over 20 years in Codes of Good Practice. The regulations define sexual harassment and indicate the obligations of the employer to take steps to prevent the conduct within its workplace. In addition to the Codes of Good Practice, the courts have continuously developed the definition of sexual harassment. Through the development by the courts, the definition of sexual harassment remains current and in line with international standards. However, important factors are not always given the same weight by judges which has led to inconsistent decisions by the courts. The definition of sexual harassment and the manner in which the court applies the definition is analysed in this thesis and compared to recent decisions in the Netherlands. The employer’s responsibility to prevent sexual harassment is regulated by the Employment Equity Act, 55 of 1998. The court's findings on whether an employer is liable for failing to prevent sexual harassment has also been developed by the courts. Through the court decisions, the obligations of the employer have been advanced and clarified. This thesis looks at the obligation of the employer to curb sexual harassment in the workplace and what further steps employers can take to assist victims who report this conduct
Submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Sexual harassment; Changing workplace; Employer's responsibility; Definition of sexual harassment; UCTD; SDG-8: Decent work and economic growth